Uchwała zgromadzenia wspólników spółki kapitałowej sprzeczna z ustawą - Frąckowiak, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
In doctrine and jurisprudence, serious doubts arise in the context of the regulations concerning the situation in which resolution of the shareholders’ meeting of a company is contrary to the law. The main problem arises due to the unexplained relationship between the resolution of the shareholders’ meeting of companies, or more broadly by the resolution of the legal and statutory bodies, and the legal act. A derivative of this dispute is the ongoing dispute over whether the decision stating the contradiction of the resolution with law is of a constitutive nature, or whether it only states that the resolution has not had any legal eff ects since its adoption.
Keywords: resolution of the shareholders’ meeting; company; legal act